2010
DOI: 10.1016/j.jallcom.2010.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Colossal electroresistance in Sm0.55Sr0.45MnO3

Abstract: We report a colossal resistance drop around insulator-metal transition temperature (TMI) in Sm0.5SSr0.4SMn03 induced by direct current. Polycrystalline samples of Sm0.5SSr0.4SMn03 were synthesized through solid state reaction method, They have been investigated by X-ray diffraction for phase evaluation, scanning electron microscopy for grain morphology and de resistivity measurement techniques for resistivity-temperature behavior. The resistivity-temperature behavior has been measured with different biasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The family of manganites are not only interesting because of their potential applications in magnetic field sensing and memory devices but also their fascinating and intriguing physics [3,4], not completely explored so far and exciting new results are emerging constantly [5,6]. The hole-doped manganites of general composition Re 1−x A x MnO 3 (Re = rare-earth metal, A = divalent alkali metal) shows the coexistence of different phases and depending on the composition and structural defects, these phases can be modified significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The family of manganites are not only interesting because of their potential applications in magnetic field sensing and memory devices but also their fascinating and intriguing physics [3,4], not completely explored so far and exciting new results are emerging constantly [5,6]. The hole-doped manganites of general composition Re 1−x A x MnO 3 (Re = rare-earth metal, A = divalent alkali metal) shows the coexistence of different phases and depending on the composition and structural defects, these phases can be modified significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The competition between coexisting AFM and FM phases resulted in the low temperature state of both the systems. The phase-separation concept was used by Mohan et al [35] to explain the resistivity data on Sm 0.55 Sr 0.45 MnO 3 . From the transport and magnetic studies on R 1−x Ca x MnO 3 (R, a rare-earth element, x = 0.88-1).…”
Section: Introductionmentioning
confidence: 99%
“…This evolution discloses the presence of the colossal electro-resistance effect in the investigated system. 68,69 Furthermore, the contribution of space charges under increasing electrical polarization confirms the dominant effect of the grain boundary region on the transport properties. In this context, Prakash et al 70 have observed a high dependence of the grain boundary resistance on the variable DC-bias.…”
Section: Resultsmentioning
confidence: 71%
“…This evolution discloses the presence of the colossal electroresistance effect in the investigated system. 68,69 Furthermore,…”
Section: Dc-bias Effectmentioning
confidence: 99%